Legal Analysis of the Enforcement of Electronic ID Cards Valid for Life Against Credit Guarantee Institutions - Handayani, Meri; Pratisto, Andito Galih; Rido, Muhammad Rasyid; Dimyati, Agus; Sutrisno, Anom (Pelopor Publikasi Akademika, 2025)
Electronic ID cards (e-KTPs) issued since 2011 or 2012 remain valid for life, even after they expire. Electronic ID cards (e-KTPs) do not need to be renewed, as they remain valid for life even after they expire. However, in practice, some banks and financial institutions still refuse to accept lifetime ID cards as a requirement for credit. This research uses both normative and empirical juridical methods to describe the issues surrounding legal awareness regarding expired e-KTPs following the issuance of Circular Letter No. 470/296/SJ concerning Electronic ID Cards (e-KTPs) with lifetime validity. In accordance with legal studies, the approach used is problem-based. To strengthen the analysis and complement secondary data, field research will be conducted to obtain primary data. The data obtained will then be presented in descriptive and conceptual form. ACC Finance as the party providing the credit guarantee will reject the customer's credit if the completeness of the credit requirements uses an expired Electronic KTP but is valid for life for fear that the customer's citizenship is unclear and is already a company provision even though based on Law Number 24 of 2013 concerning Amendments to Law Number 23 of 2006 concerning Population Administration, specifically Article 64 paragraph (7) letter a, Circular of the Minister of Home Affairs No. 470/296/SJ which states that an expired Electronic KTP is still valid and does not need to be extended because the validity period of the Electronic KTP is for life. Based on the background that has been presented, there are several problems that can be identified as follows: legal analysis of the rejection of a lifetime Electronic KTP by a credit guarantee institution as a credit requirement? and What are the legal remedies for the rejection of a lifetime E-KTP as a credit requirement by a credit guarantee institution?